2020
DOI: 10.1111/scd.12525
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of two different oral hygiene regimens on the incidence and severity of oral mucositis in pediatric patients receiving hematopoietic stem cell transplantation: A prospective interventional study

Abstract: Aims This prospective interventional study aimed to assess the efficacy of supersaturated calcium phosphate rinse and the use of an extra‐soft toothbrush twice a day when added to the existing oral hygiene protocol regimen (0.12% chlorhexidine gluconate + 3% sodium bicarbonate + nystatin 5000 U/mL) in reducing the severity of oral mucositis among pediatric patients receiving chemotherapy for the hematopoietic stem cell transplant. Methods Forty‐five patients that received chemotherapy for the hematopoietic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
0
19
1
3
Order By: Relevance
“…A systematic review and meta‐analysis revealed a negative result, wherein a decrease in the incidence of OM after performing PBM as prophylactic treatment and a reduction in the severity of OM were observed 33 . The incidence of OM in studies without prophylactic PBM protocol was higher (80%‐91.7%) than that in our results (73.5%) 19,20 . The conflicting results may reflect the methodological and protocol diversity between the studies.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A systematic review and meta‐analysis revealed a negative result, wherein a decrease in the incidence of OM after performing PBM as prophylactic treatment and a reduction in the severity of OM were observed 33 . The incidence of OM in studies without prophylactic PBM protocol was higher (80%‐91.7%) than that in our results (73.5%) 19,20 . The conflicting results may reflect the methodological and protocol diversity between the studies.…”
Section: Discussioncontrasting
confidence: 53%
“…Considering the available sample size of 49 HSCT paediatric patients and a prevalence of OM of 71%‐91.7%, 2‐5,19,20 the study had 80% power to demonstrate an absolute difference in the occurrence of OM between exposed and unexposed patients, with an alpha error of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Basic oral care is considered the backbone of supportive care for patients receiving cancer treatment, which could reduce the incidence of moderate to severe OM [4,8]. At present, mixed medication mouthwashes, which include antibacterial drugs, analgesics, vitamin B12, Xilei powder and hormone therapy, are widely used clinically [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mucositis, or mucosal barrier injury, is a condition needing supportive care characterised by erythema, atrophy and ulceration of mucous membrane anywhere along the alimentary tract as a result of cancer therapy (Sonis, 2004 ). Oral mucositis (OM) is frequently occurring treatment‐induced side effect in patients with oncological and haematological disorders (Berger et al., 2018 ; Abed et al., 2019 ; Mubaraki et al., 2020 ). Haematopoietic stem cell transplantation (HSCT) is the treatment of choice for various malignancies, immune deficiencies and bone marrow failure syndromes in children, adolescents and adults (Barriga et al., 2012 ; Copelan, 2006 ).…”
Section: Introductionmentioning
confidence: 99%